Analysis of the Operational Performance of Quay Crane Loading and Unloading at Pt. Jakarta International Container Terminal - Febricardo, Erichi Alfanso; Thamrin, M.; Saribanon, Euis (Dinasti International Journal of Digital Business Management, 2025)
Pelabunan Indonesia II (Pelindo II) is a state-owned enterprise (BUMN) that manages 12 ports in Indonesia. PT. Jakarta International Container Terminal is a subsidiary of Pelindo II. As an international terminal, PT. Jakarta International Container Terminal provides container loading and unloading services at a standart speed of 28 boxes per hour per quay crane. PT. Jakarta International Container Terminal has two docks: the west dock, with a dock length of 890 meters, a depth of 11 meters, and eight quay cranes; and the north dock, with a dock length of 720 meters, a depth of 14.5 meters, and eight quay cranes. The special case study aims to analyze and compare the performance of West Dock and North Dock based on berth occupancy ratio (BOR), gross crane rate (GCR), and vessel operation rate (VOR) per month, using secondary data from PT. Jakarta International Container Terminal with population data from September 2018 to March 2019, and vessel calls and container volumes from 2014 to 2018. The results of the data obtained from PT. Jakarta International Container Terminal describes the differences in achieving BOR, GCR, and VOR between the west dock and the north dock. The west dock has a BOR, GCR, and VOR score that is lower than the north dock, based on data from September 2018 to March 2019.